2015
DOI: 10.1039/c5ra06693j
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic characterisation of the FAD dependent monooxygenase TropB and investigation of its biotransformation potential

Abstract: Achieving regio-specific hydroxylation of aromatic compounds remains a major challenge in synthetic chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 25 publications
2
34
0
2
Order By: Relevance
“…Mechanistic and biocatalytic details on the production of hydroxylated aromatic compounds of medicinal interest were discussed and applied, resulting in the potential future exploitation of NCBs for other or improved hydroxylase-catalyzed reactions towards the regioselective oxidation of aromatic compounds or the recently applied oxidative dearomatization. [47] Experimental Section General information: All chemicals were purchased from Sigma-Aldrich (Merck) or Alfa Aesar and were used without further purification unless otherwise specified. The natural nicotinamide adenine dinucleotide coenzymes, both oxidized and reduced, were purchased from Prozomix.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic and biocatalytic details on the production of hydroxylated aromatic compounds of medicinal interest were discussed and applied, resulting in the potential future exploitation of NCBs for other or improved hydroxylase-catalyzed reactions towards the regioselective oxidation of aromatic compounds or the recently applied oxidative dearomatization. [47] Experimental Section General information: All chemicals were purchased from Sigma-Aldrich (Merck) or Alfa Aesar and were used without further purification unless otherwise specified. The natural nicotinamide adenine dinucleotide coenzymes, both oxidized and reduced, were purchased from Prozomix.…”
Section: Discussionmentioning
confidence: 99%
“…We previously established a platform for WC biocatalytic oxidative dearomatization of phenols using the flavin-dependent monooxygenase TropB (Baker Dockrey, Lukowski, Becker, & Narayan, 2018). The native biosynthetic function of TropB was first characterized by Cox and coworkers in 2012 (Abood et al, 2015;Davison et al, 2012). TropB is an oxygenase, involved in the biosynthesis of stipitatic acid, that naturally converts 3-methyl-orcinaldehyde (9) to dienone 10 with perfect site-and stereoselectivity ( Figure 2) (Abood et al, 2015;Baker Dockrey et al, 2018;Davison et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The native biosynthetic function of TropB was first characterized by Cox and coworkers in 2012 (Abood et al, 2015;Davison et al, 2012). TropB is an oxygenase, involved in the biosynthesis of stipitatic acid, that naturally converts 3-methyl-orcinaldehyde (9) to dienone 10 with perfect site-and stereoselectivity ( Figure 2) (Abood et al, 2015;Baker Dockrey et al, 2018;Davison et al, 2012). We have previously demonstrated that TropB possesses a broad substrate scope and is able to generate a diverse array of dienone products (Baker Dockrey et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dies führt unter ande-rem durch eine Diels-Alder-Cycloaddition zur Bildung des Radikalfängers Bisorbicillinol (3) [4] oder durch eine Reaktionssequenz aus Michael-Addition und Ketalisierung zu dem Inhibitor der Prostaglandin-H-Synthase-2 Tr ichodimerol (4; [5] Abbildung 1). [3] Die katalytische Aktivitätv on SorbC gegenüber einer grçßeren Auswahl an Substraten wurde vor kurzem von Narayan und Mitarbeitern getestet, wobei auch die Monooxygenasen Tr opB aus der Stiptatonsäure-Biosynthese [9] und AzaH aus der Azaphilon-Biosynthese [10] untersucht wurden, die andere Regio-und Stereoselektivitäten ermçglichen. Zum Beispiel führt eine Diels-Alder-Reaktion mit einem Vinylphenyl-Dienophil zu Sorbicatechol A( 5), [6] während die Epoxidierung von 2 (+ +)-Epoxysorbicillinol (6)ergibt [7] und eine Michael-Addition mit einem Alanin-abgeleiteten C-Nukleophil den Wegf ürdie Bildung von Sorbicillacton A( 7)b ereitet.…”
unclassified